Effect of vortex induced vibration on fatigue damage of top-tensioned riser subjected to current load - Lai, K.X. (Asian Research Publishing Network, 2017)
Over the last decade, offshore deepwater developments in the oil and gas industry have outrun the onshore and shallow water field developments. Researches, designs, and developments have been focusing on the deepwater environment in recent years. Safe and robust design of structures and systems for offshore deepwater development is relatively complicated due to the impact of high current and wave. Top tension riser (TTR), which is capable to adapt to the superior motions of the vessel, has been a reasonable and advisable option in deepwater field for transporting hydrocarbon from seabed to the platform. Hence, investigation on the effect of current on the fatigue performance of TTR in associated with vortex-induced vibration (VIV) is relatively important, considering VIV as one of the most important factors causing fatigue damage in deepwater TTR. In this study, the effect of uniform and sheared current on the VIV fatigue damage of TTR is studied. It is observed that the VIV fatigue damage increases with increasing current velocity. Besides, parameters such as water depth, riser diameter, and riser wall thickness are varied to investigate the sensitivity of the parameters in the VIV fatigue damage of TTR. The results indicated that VIV fatigue damage increases as the wall thickness increases in the bare riser; whereas the VIV fatigue damage for strake riser shows inconsistencies. Further studies and continuous validation and improvement shall be done to increase the accuracy and precision of this study. © 2006-2017 Asian Research Publishing Network (ARPN).